Method for screening oil displacement composition based on interfacial film number, screened oil displacement composition and application of screened oil displacement composition

The oil-repellent repellent compositions of nanoparticles and composite surfactants are optimized through the interface mask number screening method, which solves the problems of low recovery rate of low permeability reservoirs and poor stability of nanomaterials, and achieves efficient and economical oil-repellent repellent effect and simplifies The research and development process is applicable to large-scale promotion.

CN119274686APending Publication Date: 2025-01-07PETROCHINA CO LTD

Patent Information

Application Number
CN202411309740.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

During the oil production process, low recovery rate, difficulty in establishing a flooding system, poor stability and single functions of nanomaterials. The existing screening methods are complex, high cost and low distinction, making it difficult to effectively screen high-efficiency oil flooding combinations. Things.

Method used

Using the screening method based on the number of interface masks, the mixture of nanoparticles and composite surfactants is optimized and designed for oil-repellent oil reservoirs through interface tension, Langmuir single-molecular membrane experiment and interface expansion rheology experiment, and the oil-repellent flooding composition is simplified. R&D processes and reduce costs.

Benefits of technology

It achieves efficient oil flooding performance improvement, shortens R&D cycle, reduces costs, is suitable for large-scale promotion, and improves the recovery rate of low-permeability reservoirs, providing a cost-effective oil flooding composition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119274686A_ABST
    Figure CN119274686A_ABST
Patent Text Reader

Abstract

The invention provides a method for screening an oil displacement composition based on the number of interfacial films, the screened oil displacement composition and application of the screened oil displacement composition. The calculation formula of the number of the interfacial films is # imgabs0 #, wherein phi is the number of the interfacial films, gamma is interfacial tension, E0 is the maximum elastic modulus of the interfacial films, and theta is an interfacial expansion rheological phase angle; and screening the oil displacement composition according to the calculation formula of the interfacial film number. The oil displacement composition comprises the following components: 0.01%-0.5% of a composite surfactant; 0.001% to 0.1% of nano particles; and the balance of water. The composite surfactant comprises alkyl hydroxy sulfobetaine and an alcohol ether sulfonate anionic / nonionic surfactant. The invention provides the oil displacement composition screened based on the interfacial film number phi, the interfacial film number technology is creatively applied, an oil displacement system is optimally designed from chemical agent interface parameter properties, the research and development period is shortened, the research and development cost is reduced, complex displacement operation is avoided, and the oil displacement composition is suitable for large-scale popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of petroleum development, and relates to a method for screening an oil displacement composition based on an interface film number, the screened oil displacement composition and applications thereof, and specifically relates to a method for screening an oil displacement composition based on an interface film number, the screened oil displacement composition suitable for a low-permeability oil reservoir and applications thereof. Background Art

[0002] Low permeability reservoirs have complex pore structures, narrow throats, severe heterogeneity, and complex fractures. In addition, they have high injection pressure, poor injectivity, and difficulty in establishing an effective displacement system, which results in a low recovery rate for low permeability reservoirs. At present, low permeability reservoirs at home and abroad are mostly exploited by steam displacement and steam huff and puff. However, with the improvement of environmental protection requirements, thermal recovery will gradually be replaced by cold recovery. Therefore, chemical cold recovery is the main method for the subsequent development of low permeability reservoirs.

[0003] Surfactants play an important role in improving oil recovery. Their adsorption at the oil-water interface can reduce the interfacial tension between the displacement phase and crude oil, enhance the interaction between the oil and water phases, make the remaining crude oil in the reservoir easy to move and deform, and then emulsify into oil droplets dispersed in the displacement phase under the action of external force, thereby improving the oil washing efficiency. Both indoor experiments and field experiments have shown that the emulsification of crude oil by surfactants is very beneficial to improving the oil recovery effect (Bryan J, Kantzas A. Journal of Canadian Petroleum Technology, 2009, 48 (02): 37-46). However, the interfacial film formed by surfactants has poor strength and single function, and it is often difficult to meet the oil recovery requirements of complex reservoirs (especially low permeability reservoirs) when used alone. Therefore, the development of composite systems based on surfactants has become a research hotspot. In recent years, the application of nanomaterials in oil and gas field development has become one of the research hotspots. Studies have shown that nanomaterials have significant advantages in reducing oil-water interfacial tension, increasing structural separation pressure, changing wettability, enhancing emulsion stability, enhancing foam stability, improving mobility ratio, adsorbing asphalt precipitation, catalyzing asphalt decomposition, and inhibiting particle migration. Their combination with surfactants can further enrich their oil recovery function and improve the oil recovery effect.

[0004] Currently, commonly used nanomaterials have problems such as poor stability, single function, poor adaptability to reservoir environment, and low compatibility with surfactants. Silica and its modified products are the most studied nanoparticles in oil displacement. In addition, commonly used nanoparticles in oil displacement agents include: metal oxide nanoparticles such as aluminum oxide, ferric oxide, titanium dioxide, magnesium oxide, zinc oxide, copper oxide, as well as nanoparticles such as nanotubes, nanocellulose crystals, crystalline starch, and graphene. Hou Jirui et al. 2D intelligent "nano black card" found that nano black card can peel off the oil film during flow, forming an "oil wall", increasing flow resistance, increasing swept volume, and thus improving recovery (Oilfield Chemistry. 2020, 37(01): 133-137). Based on previous studies, it is found that poor dispersion stability of nanoparticles is a common problem. The current common solution is to modify the nanoparticles, but the modification process is cumbersome and costly, making it difficult to promote and apply. CN110437814A discloses an oil-displacing agent for improving tertiary oil recovery, and the raw materials of the oil-displacing agent include surfactant, polyacrylamide, modified nano silicon dioxide, sodium carbonate and water. The surfactant is sodium lignin sulfonate, dodecyl dimethyl hydroxypropyl sulfobetaine, fluorocarbon surfactant, and the modified silicon dioxide is γ-methacryloxypropyl trimethoxysilicon modified nano silicon dioxide. The disadvantage of the oil-displacing agent is that the recovery rate is not greatly improved, and the stability of the oil-displacing system is insufficient. Therefore, selecting nano materials that are easy to prepare and low in cost, compounding suitable surfactants, and developing new composite oil-displacing systems are still key issues to be solved in nanofluid oil displacement.

[0005] The oil displacement system screening method is an important guarantee for optimizing the design of oil displacement systems. At present, the methods for screening oil displacement systems mainly include: core flooding experimental method and visual model seepage method. The core flooding experimental method can comprehensively evaluate the influence of almost all factors, including the emulsification seepage capacity of the oil displacement system, on improving the recovery rate, but the experimental cost is high, the cycle is long, and the operation is complicated, making it difficult to carry out large-scale sample screening. The visual model seepage method for screening oil displacement systems can observe the intuitive visual results such as the seepage morphology of the emulsion in the model and the oil-water distribution, but the structure and size of the pore throat are still somewhat different from the real formation porous media; in addition, due to the limitations of processing technology and processing materials, the size of the visual model is often small, and affected by the scale effect, the oil displacement effect of different systems is low, and the screening effect of the oil displacement system is not good. Therefore, these two oil displacement system screening methods have the problems of complex operation, long experimental cycle, high cost, low differentiation of the oil displacement effect of different systems, and it is difficult to infer the mechanism of action of the displacement agent from the level of chemical agent composition properties, and it is difficult to guide the optimization design of the oil displacement system.

[0006] Therefore, in the art, it is desired to develop a simple screening method and utilize the method to screen a new and efficient oil displacement composition. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an oil recovery system composition suitable for low permeability oil reservoirs based on the interface film number technology screening, to optimize the design of the oil recovery system from the interface parameter properties of the chemical agent, to avoid complex displacement operations, to obtain an oil recovery system composition with improved oil recovery performance and increased recovery rate, and to promote the industrial application of tertiary oil recovery in low permeability oil reservoirs.

[0008] The present invention relates to a chemical flooding formula system used in tertiary oil recovery, and specifically to an oil displacement composition obtained by optimizing and designing based on an interface film number screening method, wherein nanoparticles hybridized with organic and inorganic materials are mixed with a composite surfactant and used for oil displacement in low permeability oil reservoirs, and its application in tertiary oil recovery. The present invention utilizes a screening method based on interface behavior to optimize and design a composite of nanoparticles and surfactants for oil displacement, which is of great significance for the development of new and efficient oil displacement agents.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for screening an oil displacement composition based on an interface film number, wherein the calculation formula for the interface film number is: Wherein: Φ is the interface film number, γ is the interface tension, E0 is the maximum elastic modulus of the interface film, and θ is the interface expansion rheological phase angle; the oil displacement composition is screened according to the calculation formula of the interface film number.

[0011] Compared with the existing core flooding experiment and visualization model seepage method for screening oil displacement system technology, the interface film number technology for screening oil displacement compositions provided by the present invention is free from the influence of injection and production process parameters and size effect, and only uses the interface film number Φ as an indicator for oil displacement system screening, thus avoiding complicated displacement operations, shortening the R&D cycle, reducing the R&D cost, and being suitable for large-scale sample screening.

[0012] Preferably, the interfacial tension, the maximum elastic modulus of the interfacial film, and the interfacial dilation rheological phase angle are obtained from an interfacial tension experiment, a Langmuir monomolecular film experiment, and an interfacial dilation rheological experiment, respectively.

[0013] Preferably, the interface film number is obtained by the following method:

[0014] (1) Interfacial tension experiment: Prepare an oil displacement agent aqueous solution, and measure the interfacial tension between the oil displacement agent aqueous solution and crude oil or simulated oil using a spinning drop interfacial tension meter (for example, see Acta Physico-Chimica Sinica, 2009, 25(1): 41-46);

[0015] (2) Langmuir monolayer experiment: Prepare an organic solvent solution of the oil displacement agent and drip it onto the surface of the water tank of the Langmuir film analyzer. After the organic solvent evaporates, use the Langmuir monolayer experiment (for example, see: Journal of Atmospheric and Environmental Optics. 2022, 17(01): 171-184) to measure the change of surface tension with the average molecular area, obtain the π-A isotherm, and obtain the maximum elastic modulus of the interfacial film;

[0016] (3) Interface dilation rheology experiment: prepare an oil-displacing agent aqueous solution, and use a droplet shape analysis method (for example, see Journal of Tianjin Polytechnic University, 2023, 42(02): 34-41) to measure the interface dilation rheological phase angle between the oil-displacing agent aqueous solution and crude oil or simulated oil;

[0017] (4) Based on the interfacial tension, the maximum elastic modulus of the interfacial film and the interfacial expansion rheological phase angle, the interfacial film number is proposed:

[0018] The oil displacement process is essentially an interfacial process. Therefore, starting from the interface adsorption layer of the oil displacement system, developing a method for screening the oil displacement system based on specific interface parameters can solve the problem that the influencing factors of the current indoor evaluation experiments are too complex, making it difficult to effectively screen the oil displacement system.

[0019] Preferably, step (3) specifically includes the following steps: preparing an oil-displacing agent aqueous solution; determining the interfacial expansion rheological properties between the oil-displacing agent aqueous solution and crude oil or simulated oil by a droplet shape analysis method, that is, after the oil droplets are formed, the oil droplets are subjected to a sinusoidal periodic disturbance at a certain operating frequency; and obtaining the interfacial expansion rheological phase angle based on the phase difference between the interfacial tension sinusoidal periodic curve and the interfacial area sinusoidal periodic curve.

[0020] Preferably, the certain operating frequency is 0.1-0.2 Hz, such as 0.1 Hz, 0.15 Hz, 0.2 Hz, etc.

[0021] Preferably, the oil-displacing agent in the oil-displacing agent aqueous solution in step (1) and step (3) and the oil-displacing agent in the oil-displacing agent organic solvent solution in step (2) includes any one of sweet 1-B18, sweet 3-B26PS, anion non-B26PS, secondary alkylbenzene sulfonate, petroleum sulfonate, AEO9, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate, or a combination of at least two thereof.

[0022] The interfacial film number (φ) used in the present invention is an interfacial performance parameter reflecting the comprehensive interfacial properties of the chemical system.

[0023] The value of the interface film number is closely related to the oil displacement effect, and there is a linear one-to-one correspondence between the interface film number φ and the enhanced oil recovery EOR, which can be used as a comprehensive parameter to characterize the interface properties of oil displacement chemicals. The lower the interfacial tension, the higher the interfacial film strength, and the better the interfacial viscoelasticity, the larger the φ value is, and the better the displacement effect is. When the interface film number is less than 550, the enhanced oil recovery value is less than 15%; and when the interface film number is greater than or equal to 550, the enhanced oil recovery is greater than 15%; the interface film number continues to increase, and the recovery rate increases slowly. Based on this, the interface film value of 550 is used as a standard for evaluating the oil displacement effect of chemical agents. On this basis, the present invention obtains an oil displacement composition system for low permeability reservoirs with an interface film value of ≥550 and high oil displacement efficiency.

[0024] In a second aspect, the present invention provides an oil displacement composition screened based on the number of interfacial films, wherein the oil displacement composition comprises the following components by weight percentage:

[0025] Complex surfactant 0.01%-0.5%;

[0026] Nanoparticles 0.001%-0.1%;

[0027] The rest is water;

[0028] The composite surfactant comprises alkyl hydroxysulfobetaine and alcohol ether sulfonate anionic non-surfactant.

[0029] The present invention provides an oil displacement composition suitable for low permeability oil reservoirs screened based on the interface film number φ technology, creatively applies the interface film number technology, optimizes the design of the oil displacement system from the interface parameter properties of the chemical agent, shortens the research and development cycle, reduces the research and development cost, avoids complex displacement operations, and is suitable for large-scale promotion. The present invention specifically provides an oil displacement system composition containing a composite surfactant and modified alumina nanoparticles with a high recovery rate obtained through the interface film number.

[0030] In the present invention, the amount of the complex surfactant in the oil-displacing composition can be 0.01%, 0.03%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, etc., the amount of the nanoparticles can be 0.001%, 0.003%, 0.005%, 0.008%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, etc., and the rest is water.

[0031] Preferably, the alkylhydroxysulfonyl betaine comprises a linear or branched alkyl or aralkylhydroxysulfonyl betaine having an alkyl carbon number of 16-26 (eg, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26).

[0032] Preferably, the alkylhydroxysulfonate includes aralkylhydroxysulfonate having a branched alkyl group with 22 carbon atoms (10-(3,5-dimethyl)-C22 alkylhydroxysulfonate).

[0033] Preferably, the carbon number of the fatty alcohol in the alcohol ether sulfonate anionic non-surfactant is 8-26 (e.g., 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, etc.) and the carbon number of the polyoxypropylene and polyoxyethylene is 5-20, e.g., 5, 8, 10, 12, 14, 16, 18, 20, etc.

[0034] Preferably, the alcohol ether sulfonate anionic non-surfactant comprises C 18 PO 10 EO6SO3Na.

[0035] The mass ratio of the alkyl hydroxysulfobetaine to the alcohol ether sulfonate anionic non-surfactant is 8:2-3:7, such as 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, etc., preferably 7:3-4:6, and more preferably 5:5.

[0036] Preferably, the nanoparticles include any one of partially hydrophobically modified alumina with polyacrylamide, methylated modified silica, unmodified silica or ferric oxide, or a combination of at least two thereof, preferably partially hydrophobically modified alumina with polyacrylamide.

[0037] Preferably, the partially hydrophobically modified aluminum oxide by polyacrylamide comprises 50% hydrophobically modified aluminum oxide by polyacrylamide. The 50% hydrophobically modified aluminum oxide by polyacrylamide means that the amount of the polyacrylamide is 50% based on the total weight of the polyacrylamide and the aluminum oxide being 100%.

[0038] Preferably, the particle size of the nanoparticles is 10-80 nm, for example, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, etc., preferably 15-70 nm, and more preferably 20 nm.

[0039] Preferably, the water comprises any one of oilfield injection wastewater, formation water or clean water, or a combination of at least two of them.

[0040] Preferably, the mineralization of the water is less than 100,000 mg / L, for example 90,000 mg / L, 80,000 mg / L, 70,000 mg / L, 60,000 mg / L, 50,000 mg / L, 40,000 mg / L, 30,000 mg / L, 20,000 mg / L, 10,000 mg / L, 8,000 mg / L, 5,000 mg / L, etc.

[0041] As a preferred technical solution of the present invention, the oil displacement composition comprises the following components by weight percentage:

[0042] Complex surfactant 0.01%-0.2%;

[0043] Nanoparticles 0.001%-0.01%;

[0044] The rest is water.

[0045] As a further preferred technical solution of the present invention, the oil displacement composition comprises the following components by weight percentage:

[0046] Complex surfactant 0.15%;

[0047] Nanoparticles 0.005%;

[0048] The rest is water.

[0049] Preferably, the interfacial film number of the oil-displacing composition is ≥550, for example, 600, 800, 1000, 3000, 5000, 8000, etc.

[0050] The oil displacement composition system for low permeability reservoirs provided by the present invention adopts 10-(3,5-dimethyl)-C22 alkyl hydroxysulfobetaine, C 18 PO 10 The present invention is composed of alumina nanoparticles hydrophobically modified with EO6SO3Na and part of polyacrylamide, and its interfacial properties have reached ultra-low interfacial tension and excellent emulsification properties. The core flooding experiment shows that the low permeability reservoir flooding composition system provided by the present invention adopts branched C 22 Arylalkyl hydroxysulfobetaine, C 18 PO 10 The oil recovery system composed of EO6SO3Na and partially polyacrylamide hydrophobically modified alumina nanoparticles has high oil recovery efficiency and low dosage, and thus has the dual advantages of lower economic cost and higher oil recovery efficiency.

[0051] In a third aspect, the present invention provides an application of the oil displacement composition screened based on interface film number as described in the second aspect in tertiary oil recovery.

[0052] Compared with the prior art, the present invention has at least the following beneficial effects:

[0053] The present invention provides an oil displacement composition suitable for low permeability oil reservoirs screened based on the interface film number Φ technology, creatively applies the interface film number technology, optimizes the design of the oil displacement system from the interface parameter properties of the chemical agent, shortens the research and development cycle, reduces the research and development cost, avoids complex displacement operations, and is suitable for large-scale promotion. The present invention specifically provides an oil displacement system composition containing a composite surfactant and modified alumina nanoparticles with a high recovery rate obtained through the interface film number. DETAILED DESCRIPTION

[0054] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0055] Example 1: Interfacial Film Number Test of Surfactant

[0056] This example measures the interfacial film number of different surfactants, and the test process is as follows:

[0057] (1) Interfacial tension test method: A 0.2% mass concentration of an oil displacement agent aqueous solution was prepared, and the interfacial tension between the oil displacement agent aqueous solution and crude oil was measured using a TX500C interfacial tension tester using a spinning drop method. The test temperature was 90° C. and the rotation speed was 5000 RPM.

[0058] (2) Langmuir monolayer experimental test method: prepare an organic solvent solution of oil displacement agent with a mass concentration of 0.1% (wherein the organic solvent is chloroform), and drip it onto the surface of the water tank of the Langmuir film analyzer. After the organic solvent evaporates, use the Langmuir monolayer experiment to measure the change of surface tension with the average molecular area, obtain the π-A isotherm, and obtain the maximum elastic modulus of the interfacial film.

[0059] (3) Interface dilation rheology test method: Prepare an oil displacement agent aqueous solution with a mass concentration of 0.2%, and use droplet shape analysis to measure the interface dilation rheology properties between the oil displacement agent aqueous solution and crude oil or simulated oil.

[0060] (4) Combining the above parameters, using the formula Φ = E0 (tanθ) 0.90 / γ 1.12 The interfacial film number was calculated, and the test results of the interfacial film number of different surfactants are shown in Table 1.

[0061] Table 1

[0062]

[0063] As can be seen from Table 1, 10-(3,5-dimethyl)-C22 alkylhydroxysulfobetaine has the largest interfacial film number of 1193.73, C 18 PO 10 The interfacial film number of EO6SO3Na is 945.54, therefore, 10-(3,5-dimethyl)-C22 alkylhydroxysulfobetaine and C 18 PO 10 EO6SO3Na as surfactant complex.

[0064] Example 2: Results of interfacial film number of surfactant complexes with different compounding ratios

[0065] This example studies the different mass ratios of 10-(3,5-dimethyl)-C22 alkyl hydroxysulfobetaine and C 18 PO 10 The interfacial film number test of the EO6SO4Na surfactant complex was carried out in the same manner as in Example 1. The test results are shown in Table 2.

[0066] Table 2

[0067]

[0068] It can be seen from Table 2 that the interfacial film numbers of different compound surfactant systems are very different. 18 PO 10 When the ratio of EO6SO3Na is between 8:2 and 3:7, the number of interfacial films is between 2000 and 5000, and the interfacial tension is also low. When the ratio of the two is 5:5, the number of interfacial films reaches the maximum. Therefore, the optimal ratio is selected, 10-(3,5-dimethyl)-C22 alkyl hydroxysulfobetaine: C 18 PO 10 The mass ratio of EO6SO3Na is 5:5.

[0069] Example 3: Test on the effect of nanoparticles on the interfacial film number of surfactant composition

[0070] In this example, the nanoparticles were used to treat 10-(3,5-dimethyl)-C22 alkylhydroxysulfobetaine and C 18 PO 10 The effect of the interfacial film number on the composite surfactant composed of EO6SO4Na in a mass ratio of 5:5 (wherein the weight percentage of the composite surfactant is 0.2%, and the weight percentage of the nanoparticles is shown in Table 3) was tested. The test operation referred to Example 1, and the test results are shown in Table 3.

[0071] Table 3

[0072]

[0073] As can be seen from Table 3, under the same nanoparticle concentration, the interface film number of the aluminum oxide system with 50% polyacrylamide hydrophobically modified is the highest, and the interface film value of ferric oxide is the lowest, and the mass concentration of aluminum oxide with 50% polyacrylamide hydrophobically modified is between 0.005-0.01%, and the system with a particle size of 10nm and 20nm has a higher interface film number. Therefore, the aluminum oxide with 50% polyacrylamide hydrophobically modified nanoparticles is preferably selected, and the optimal concentration is 0.005% and the particle size is 20nm.

[0074] Example 4: Test on the influence of interfacial tension of different oil displacement composition systems

[0075] This example tests the effect of temperature and salinity on the interfacial tension of the oil displacement system composition. The oil displacement system is 10-(3,5-dimethyl)-C22 alkyl hydroxysulfobetaine and C 18 PO 10 The mass ratio of EO6SO3Na is 5:5, and the nanoparticles are 50% polyacrylamide hydrophobically modified alumina. Interfacial tension test: Formation water with a mineralization of 5000-200000 mg / L is used. The specific mass concentration of the composite surfactant is shown in Table 4. The concentration of 50% polyacrylamide hydrophobically modified alumina is 0.005% solution. The particle size of the nanoparticles is 20nm. The interfacial tension of the above solution is tested by the rotating drop method using a TX500C interfacial tension tester. The test temperature is 50-120°C and the rotation speed is 5000RPM. The test results are shown in Table 4.

[0076] Table 4

[0077]

[0078] It can be seen from Table 4 that in the range of 50-120°C, when the mass concentration of the composite surfactant is 0.05%-0.2% and the mineralization is 5000-140000 mg / L, the interfacial tension of the oil displacement system reaches ultra-low interfacial tension.

[0079] Example 5: Emulsification performance test of oil displacement composition system

[0080] This example tests the emulsification performance of the composition for oil displacement system.

[0081] Test method: Formation water with different mineralizations was used to prepare composite surfactant / nanoparticle solutions, where the oil displacement system was 10-(3,5-dimethyl)-C22 alkylhydroxysulfobetaine and C 18 PO 10The mass ratio of EO6SO3Na is 5:5, and the nanoparticles are 50% polyacrylamide hydrophobically modified alumina. The concentration of the composite surfactant is 0.15wt%, the mass concentration of the nanoparticles is 0.005%, and the rest is formation water with different mineralization. Crude oil is mixed with the composite surfactant / nanoparticle solution in a mass ratio of 1:1, and the prepared solution is poured into a sealed bottle. The HZ-8812S water bath reciprocating constant temperature oscillator is used to oscillate at a speed of 90rpm for 6 hours. After standing for 72 hours, the stratification of the system is observed. The test temperature is 90℃. The experimental results are shown in Table 5.

[0082] Table 5

[0083] Mineralization(mg / L) Middle phase microemulsion volume 500 10 1000 12 5000 10 10000 13 50000 17 70000 16 100000 18 150000 9 170000 8 200000 8

[0084] It can be seen from Table 5 that for oil displacement systems with different salinities, the oil-water system forms a certain amount of middle phase microemulsion, which is Winsor III type, and has the unique property of being able to solubilize both oil and water, and the interfacial tension between the oil phase and the water phase is extremely low. The higher the proportion of the middle phase microemulsion, the stronger the emulsification ability. The volume of the middle phase microemulsion increases first and then decreases with the increase of salinity. When the salinity is 100000 mg / L, the volume of the middle phase microemulsion is the largest, indicating that this system has the best emulsification effect.

[0085] Example 6: Study on oil displacement efficiency of oil displacement system composition

[0086] The core flooding experiment was conducted in accordance with the petroleum industry standard SY / T 6424-2000 composite flooding system performance test method. The basic procedure is: core evacuation, saturation with formation water - water phase permeability measurement - saturation with crude oil to create bound water - water flooding to 98% water content - injection of chemical flooding slugs - subsequent conversion to formation water flooding to 98% water content. The experimental temperature was 90°C, and formation water with a salinity of 90,000 mg / L was used.

[0087] The material composition of the main slug flooding agent formula of the No. 1-4 flooding experimental group is shown in Table 6. The composite surfactant is 10-(3,5-dimethyl)-C22 alkyl hydroxysulfobetaine and C 18 PO 10 The mass ratio of EO6SO3Na is 5:5, and the nanoparticles are 50% polyacrylamide hydrophobically modified aluminum oxide. The mass concentrations of specific substances and the experimental results are shown in Table 6.

[0088] Table 6

[0089]

[0090] It can be seen from Table 6 that the further enhanced oil recovery of experimental group 1 after water flooding is only 4.28%, and the composite surfactants with a mass ratio of 6:4 and 5:5 are 10-(3,5-dimethyl)-C22 alkyl hydroxysulfobetaine and C 18 PO 10 The recovery rate of EO6SO3Na after water flooding can reach 12.45% and 15.09%. After adding 0.005% nanoparticles to the composite flooding composition of experimental group 4, its recovery rate after water flooding can reach 20.24%, which has obvious advantages in improving recovery rate.

[0091] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the method for screening oil displacement compositions based on the number of interfacial films, the screened oil displacement compositions and their applications, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for screening an oil displacement composition based on an interfacial film number, characterized in that: The calculation formula of the interface film number is: Wherein: Φ is the interface film number, γ is the interface tension, E0 is the maximum elastic modulus of the interface film, and θ is the interface expansion rheological phase angle; the oil displacement composition is screened according to the calculation formula of the interface film number.

2. The method for screening an oil displacement composition based on an interface film number according to claim 1, characterized in that: The interfacial tension, the maximum elastic modulus of the interfacial film, and the interfacial dilation rheological phase angle are obtained from interfacial tension experiments, Langmuir monomolecular film experiments, and interfacial dilation rheological experiments, respectively.

3. The method for screening an oil displacement composition based on the interface film number according to claim 1 or 2, characterized in that: The interfacial film number is obtained by the following method: (1) Interfacial tension experiment: Prepare an oil displacement agent aqueous solution and measure the interfacial tension between the oil displacement agent aqueous solution and crude oil or simulated oil using a spinning drop interfacial tension meter; (2) Langmuir monolayer experiment: Prepare an organic solvent solution of the oil displacement agent and drip it onto the surface of the water tank of the Langmuir film analyzer. After the organic solvent evaporates, use the Langmuir monolayer experiment to measure the change of surface tension with the average molecular area, obtain the π-A isotherm, and obtain the maximum elastic modulus of the interfacial film; (3) Interface dilation rheology experiment: Prepare an oil displacement agent aqueous solution, and use the droplet shape analysis method to measure the interface dilation rheological phase angle between the oil displacement agent aqueous solution and crude oil or simulated oil; (4) Based on the interfacial tension, the maximum elastic modulus of the interfacial film and the interfacial expansion rheological phase angle, the interfacial film number is proposed:

4. The method for screening an oil displacement composition based on an interface film number according to claim 3, characterized in that: Step (3) specifically includes the following steps: preparing an oil-displacing agent aqueous solution; determining the interfacial expansion rheological properties between the oil-displacing agent aqueous solution and crude oil or simulated oil by using a droplet shape analysis method, that is, after the oil droplets are formed, the oil droplets are subjected to a sinusoidal periodic disturbance at a certain operating frequency; and obtaining the interfacial expansion rheological phase angle based on the phase difference between the interfacial tension sinusoidal periodic curve and the interfacial area sinusoidal periodic curve; Preferably, the certain operating frequency is 0.1-0.2 Hz; Preferably, the oil-displacing agent in the oil-displacing agent aqueous solution in step (1) and step (3) and the oil-displacing agent in the oil-displacing agent organic solvent solution in step (2) includes any one of sweet 1-B18, sweet 3-B26PS, anion non-B26PS, secondary alkylbenzene sulfonate, petroleum sulfonate, AEO9, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate, or a combination of at least two thereof.

5. An oil displacement composition based on interface film number screening, characterized in that: The oil displacement composition comprises the following components by weight percentage: Complex surfactant 0.01%-0.5%; Nanoparticles 0.001%-0.1%; The rest is water; The composite surfactant comprises alkyl hydroxysulfobetaine and alcohol ether sulfonate anionic non-surfactant; The number of interface films is the number of interface films as claimed in claim 1.

6. The oil displacement composition based on interface film number screening according to claim 5, characterized in that, The alkyl hydroxysulfobetaine includes a linear or branched alkyl or aralkyl hydroxysulfobetaine having an alkyl carbon number of 16-26; Preferably, the alkylhydroxysulfonyl betaine comprises an aralkylhydroxysulfonyl betaine having a branched alkyl group with a carbon number of 22; Preferably, the carbon number of the fatty alcohol in the alcohol ether sulfonate anionic non-surfactant is 8-26 and the carbon number of the polyoxypropylene and polyoxyethylene is 5-20; Preferably, the alcohol ether sulfonate anionic non-surfactant comprises C 18 PO 10 EO6SO3Na; The mass ratio of the alkyl hydroxysulfobetaine to the alcohol ether sulfonate anionic non-surfactant is 8:2 to 3:7, preferably 7:3 to 4:6, and more preferably 5:

5.

7. The oil displacement composition based on interface film number screening according to claim 5 or 6, characterized in that, The nanoparticles include any one or a combination of at least two of partially hydrophobically modified alumina with polyacrylamide, methylated modified silica, unmodified silica or ferric oxide, preferably partially hydrophobically modified alumina with polyacrylamide; Preferably, the partially polyacrylamide hydrophobically modified alumina comprises 50% polyacrylamide hydrophobically modified alumina; Preferably, the particle size of the nanoparticles is 10-80 nm, preferably 15-70 nm, and further preferably 20 nm; Preferably, the water comprises any one or a combination of at least two of oilfield injection wastewater, formation water or clean water; Preferably, the mineralization of the water is less than 100,000 mg / L.

8. The oil displacement composition based on interface film number screening according to any one of claims 5-7, characterized in that, The oil displacement composition comprises the following components by weight percentage: Complex surfactant 0.01%-0.2%; Nanoparticles 0.001%-0.01%; The rest is water; Further preferably, the oil displacement composition comprises the following components by weight percentage: Complex surfactant 0.15%; Nanoparticles 0.005%; The rest is water.

9. The oil displacement composition based on interface film number screening according to any one of claims 5-8, characterized in that, The interfacial film number of the oil displacement composition is ≥550.

10. Use of the oil displacement composition based on interface film number screening as claimed in any one of claims 5 to 9 in tertiary oil recovery.

Citation Information

Patent Citations

  • High-recovery-ratio tertiary oil recovery displacement agent

    CN110437814A

Cited By

  • Oil displacement system screening method based on monomolecular film characterization and application thereof

    CN119246338A

  • Screening method for oil displacement system based on single-molecule membrane characterization and application thereof

    CN119246338B

  • Preparation method and application of zinc oxide nanoparticle stable micro-nano foam system

    CN121592328A

  • Application of compound composition in crude oil recovery of high-temperature and high-salt oil reservoir

    CN122213960A